Fiscal policy, interest rates and risk premia in open economy - Salvatore Dell'Erba; Sergio Sola (Graduate Institute of International and Development Studies, 2011)
This paper reconsiders the effects of fiscal policy on long-term interest rates and sovereign spreads employing a Factor Augmented Panel (FAP) to control for the presence of common unobservable factors. We construct a real-time dataset of macroeconomic and fiscal variables for a panel of OECD countries for the period 1989-2009. We find that two global factors - the global monetary and fiscal policy stances - explain more than 60% of the variance in the long-term interest rates. The same two global factors play a relevant role also in explaining the variance of sovereign spreads, which in addition respond to global risk aversion. With respect to standard estimation techniques the use of the FAP reduces the importance of domestic fiscal variables in explaining long- term interest rates, while it emphasizes their importance in explaining sovereign spreads. Using the FAP framework we also analyse the cross-country differences in the propagation of a shock to global fiscal stance and global risk aversion. We find the effects of the former to be modest in large economies and strong in economies characterized by low financial integration and current account deficits. Changes in global risk aversion, instead, lead to higher spreads in countries with a high stock of public debt and weaker political institutions.
Keywords: C10; E43; F42; F62; H68; 330; fiscal policy; sovereign debt; interest rates; sovereign spreads; real time data; cross-sectional dependence; heterogeneous panels; factor model; Finanzpolitik; Öffentliche Schulden; Zins; Öffentliche Anleihe; Panel; OECD-Staaten